PERFIL GLICÊMICO DOS FUNCIONÁRIOS DA UNIVERSIDADE REGIONAL DO NOROESTE DO ESTADO DO RIO GRANDE DO SUL – UNIJUÍ - 2009 - Schneider, Aline; Gonçalves, Darlan; Fritzen, Janaina; Pletsch, Marilei U. (Salão do Conhecimento, 2013)
Resumo